Media representation and the global imagination - Orgad, Shani 1972- (Global media and communication., 2012)
This book is a clear, systematic, original and lively account of how media representations shape the way we see our and others' lives in a global age. It provides in-depth analysis of a range of international media representations of disaster, war, conflict, migration, and celebration. The book explores how images, stories, and voices, on television, the Internet, and in advertisements and newspapers invite us daily to relocate to distant contexts, and to relate to people who are remote from our daily lives by developing "mediated intimacy" and focusing on the self. It also explores how these representations shape our self-narratives. Orgad examines five sites of media representation - the other, the nation, possible lives, the world, the self. She argues that representations can and should contribute to fostering more ambivalence and complexity in how we think and feel about the world, our place in it, and our relation to far-away others. -- Back cover.